2019
DOI: 10.1111/jvh.13112
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus testing, liver disease assessment and direct‐acting antiviral treatment uptake and outcomes in a service for people who are homeless in Sydney, Australia: The LiveRLife homelessness study

Abstract: People who are homeless have increased hepatitis C virus (HCV) infection risk, and are less likely to access primary healthcare. We aimed to evaluate HCV RNA prevalence, liver disease burden, linkage to care and treatment uptake and outcomes among people attending a homelessness service in Sydney. Participants were enrolled in an observational cohort study with recruitment at a homelessness service over eight liver health campaign days. Finger-stick whole-blood samples for Xpert® HCV Viral Load and venepunctur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…Amongst PWID and other vulnerable populations, rapid testing has been shown to substantially increase coverage and referral rates . To date, many services have not been developed for vulnerable populations such as the homeless, PWID and prisoners, which must both contend with numerous social determinants that contribute to poor quality of life and poor social functioning as well as health inequalities . It should be emphasized that HCV treatment should be offered based on clinical rather than social factors or injecting‐related behaviours , underlining the necessity of overcoming obstacles to HCV treatment delivery to PWID.…”
Section: The Model Of Care (Moc): a Tool For Increasing Treatment Covmentioning
confidence: 99%
“…Amongst PWID and other vulnerable populations, rapid testing has been shown to substantially increase coverage and referral rates . To date, many services have not been developed for vulnerable populations such as the homeless, PWID and prisoners, which must both contend with numerous social determinants that contribute to poor quality of life and poor social functioning as well as health inequalities . It should be emphasized that HCV treatment should be offered based on clinical rather than social factors or injecting‐related behaviours , underlining the necessity of overcoming obstacles to HCV treatment delivery to PWID.…”
Section: The Model Of Care (Moc): a Tool For Increasing Treatment Covmentioning
confidence: 99%
“…Homelessness was another signi cant competing priority among PWID. Previous work has shown that homeless people often face numerous complex issues including but not limited to domestic violence, mental illness, and addiction disorders (47)(48)(49) and are less likely to be linked to general practitioners or to receive healthcare than the general population (50,51). This is while the national evidence suggests that homeless people are at increased risk of HIV and HCV infections (52)(53)(54)).…”
Section: Discussionmentioning
confidence: 99%
“…Homelessness was found to be another significant competing priority among PWID. Previous work has shown that homeless people often face numerous complex issues including but not limited to domestic violence, mental illness, and addiction disorders (47)(48)(49) and are less likely to be linked to general practitioners or to receive healthcare than the general population (50,51). This is while the national evidence suggests that homeless people are at increased risk of HIV and HCV infections (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%